A previdência em carne e osso - Teixeira, Marcio França (2008)
Search This search, from a reading of the historical evolution of the legislation are highlighted Previdenciária where all constitutional amendments, compared examine the benefits of retirees by the General Rules and by the Owner. The main analysis is to show, through subject of meat and bone, how does the benefits and finds that its decline is in economic terms. Finally, the poll showed what other consequences the decrease in benefits brings to the subject of meat and bone